Targeting prosurvival BCL2 signaling through Akt blockade sensitizes castration‐resistant prostate cancer cells to enzalutamide. Issue 11 (22nd June 2019) - Pilling, Amanda B.; Hwang, Clara
Abstract: Background: Prostate cancer that recurs after initial treatment inevitably progresses to castration‐resistant prostate cancer (CRPC), the lethal stage of the disease. Despite improvements in outcomes from next generation androgen receptor (AR)‐axis inhibitors, CRPC remains incurable. Therapeutic strategies to target AR antagonist resistance are urgently needed to improve outcomes for men with this lethal form of prostate cancer. Methods: Apoptosis and BCL2 family signaling were characterized in cell line models of CRPC. Quantitative real‐time polymerase chain reaction and Western blot analysis were used to determine BCL2 expression levels. Drug sensitivity was determined by proliferation, survival and apoptosis analysis. Protein‐protein interactions were evaluated by coimmunoprecipitation followed by Western blot detection. Results: In the present study, we identify antiapoptotic BCL2 protein signaling as a mechanism of resistance to AR antagonist enzalutamide. In CRPC cell line models, we found that BCL‐xL and MCL‐1 proteins block apoptosis through binding and sequestering proapoptotic proteins BIM and BAX, resulting in cell survival in response to enzalutamide. Treatment with BH3‐mimetics targeting BCL‐xL or MCL‐1 disrupts these interactions and activates apoptosis, sensitizing CRPC cells to enzalutamide. Importantly, we demonstrate that PI3K/Akt signaling is activated in response to enzalutamide and mediates apoptosis evasion through inactivation of BAD, a BH3‐only protein that activates proapoptotic signlaing through inhbition of BCL‐xL. Inhibition of Akt activates BAD, resulting in increased apoptosis and sensitivity to enzalutamide, demonstrating an alternative therapeutic strategy to target drug resistance. Conclusions: These results demonstrate that CRPC cells employ multiple mechanisms to mediate apoptosis evasion through BCL2 signaling, suggesting this pathway is critical for survival. This study provides a strong preclinical rationale for developing therapeutic strategies to target antiapoptotic BCL2 signaling in combination with AR antagonists to improve treatment options for patients with advanced prostate cancer.